Assessing the effectiveness of progressive taxation in emerging economic landscapes - Kalhapure, Balasaheb; Thavara, Shabbirali S.; Pavithra, S; Manoj Kumar, R; Gupta, Rakhi; Jain, Sweety (The International tax journal, 2026)
The idea of progressive taxation is generally seen as one of the most important fiscal tools to decrease income inequality and achieve inclusive growth, especially in developing economies with structural change and fiscal limitations. This paper reviews the efficiency of progressive taxation using the developing economic environment as a lens by noting its effect on the distribution of income, mobilization of revenue and efficiency of the economy. The study is based on a mixed-methods approach where a panel analysis of the emerging economies is mixed with comparative country-level information on the interaction between tax progressivity and informality, the quality of governance, and public spending. The empirical results indicate statistically significant negative correlation between tax progressivity and post tax income inequality wherein one percentage rate of increment on top marginal tax rate decreases the Gini coefficient by 0.3 to 0.5 percentage points. Moderate progressivity is also associated with increased and more predictable tax collections of 1819 percent of GDP together with excessive high rates with diminishing returns on account of avoidance and compliance costs. The findings also show that redistributive outcomes are enhanced by the presence of good institutions and reinvestment of tax revenues on human capital.